Indigeneous Communal Pastoral in the Dalihan Natolu Kinship System - Robinson Simanungkalit (LPPM IAKN Tarutung, 2022)
The Communal-indigenous Pastoral Paradigm is a pastoral theology attempt in the encounter of between Communal Pastoral Theology and the Dalihan Natolu kinship system of Batak culture. Indigenous Communal Pastoral is originally rooted and born from the local wisdom designed for the society and socio-culture of a community that has a system of values and beliefs as well as philosophies. These values and philosophies can be assimilated and integrated to build a contextualised pastoral approach. Indigenous Communal Pastoral combines and adjusts existing customary and cultural approaches and dialogues them with the perspective of Pastoral Theology. The research method used in this study is descriptive qualitative research method through literature study. The purpose of writing this article is to see how Indigeneous Communal Pastoral in the Dalihan Natolu kinship system as a form of local wisdom of Batak ancestral heritage represents pastoral assistance.